Timeline analysis of IgA and IgG levels in Covid-19 hospitalized patients according to the clinical outcome - Thalia Medeiros; Fabiana R. Carvalho; Renan Faustino; Gabriel M. C. Guimarães; Lilian S. Alves; Any Caroline Oliveira; Elzinandes L. Azeredo; Jorge R. Almeida; Luzia Maria O. Pinto; Andrea Alice Silva (Sociedade Brasileira de Patologia Clínica, 2021)
ABSTRACT Introduction: Studies suggest the association between antibody production and the severity of coronavirus disease 2019 (Covid-19). Objectives: To evaluate the concentrations of immunoglobulins class A (IgA) and class G (IgG) during the hospitalization period of Covid-19 patients according to the outcome (survival vs death). Materials and methods: Patients with severe acute respiratory syndrome of coronavirus 2 (Sars-CoV-2) infection confirmed by reverse transcriptase reaction followed by polymerase chain reaction (RT-PCR) were included in this prospective study. Samples were obtained weekly during the follow-up of individuals, considering symptom onset. Titers of anti-Sars-CoV-2 IgA and IgG were measured using a commercial immunoassay. Correlations between IgA/IgG and cycle threshold (Ct) values for N1 and N2 target genes were also assessed. Results: We studied 55 Covid-19 patients (59.7±16.2 years, 63.6% male), of which 28 (50.9%) died. We observed IgA and IgG positivity (IgA+ and IgG+) in 90.9% and 80% of patients, respectively. The highest IgA+ frequency was observed at weeks 2 and 3 and the highest IgG+ at weeks 3 and 4. It is important to note that patients who died presented lower IgA titers in the first two weeks (p < 0.05); however, a significant increase in IgA levels was observed in the subsequent weeks. Lastly, we identified that significant correlations between Ct values and immunoglobulins levels, both IgA and IgG were correlated with Ct N2 in patients who died. Conclusion: Our results suggest that lower IgA titers in early Covid-19, which is associated with lower Ct values, may indicate patients at higher risk for death.